1985
DOI: 10.1083/jcb.101.5.1690
|View full text |Cite
|
Sign up to set email alerts
|

Wheat germ agglutinin blocks the biological effects of nerve growth factor.

Abstract: The binding of nerve growth factor (NGF) to specific cell surface receptors initiates a variety of effects that lead to the morphological and biochemical differentiation of clonal pheochromocytoma, PC12, cells. The lectin wheat germ agglutinin (WGA) alters the characteristics of NGF-receptor interaction. We have found that treatment of PC12 cells with WGA dramatically and reversibly inhibits the ability of NGF to elicit three distinct biological effects characteristic of NGF action. Two of these events, the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In the present study, we demonstrate that wheat germ ag lu and PG12 production by HUVEC, whereas other lectins with different sugar specificities are ineffective. Because previous studies have demonstrated that WGA does not bind to or inactivate thrombin (Ganguly et al, 19791, it is most likely that WGA either interferes with the binding of thrombin to its binding site or inhibits tional state of the binding site(s), because WGA has been shown to modulate the affinity of nerve growth factor (NGF) receptors for NGF (Buxer et al, 1983) and block the biological effects of NGF (Landrath et al, 1985). The specificity of WGA is relative rather than absolute.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, we demonstrate that wheat germ ag lu and PG12 production by HUVEC, whereas other lectins with different sugar specificities are ineffective. Because previous studies have demonstrated that WGA does not bind to or inactivate thrombin (Ganguly et al, 19791, it is most likely that WGA either interferes with the binding of thrombin to its binding site or inhibits tional state of the binding site(s), because WGA has been shown to modulate the affinity of nerve growth factor (NGF) receptors for NGF (Buxer et al, 1983) and block the biological effects of NGF (Landrath et al, 1985). The specificity of WGA is relative rather than absolute.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, WGA may block thrombin-induced rises in [Ca2+li by altering the func-A Histamine HBS . c WGA 4 tional state of the binding site(s), because WGA has been shown to modulate the affinity of nerve growth factor (NGF) receptors for NGF (Buxer et al, 1983) and block the biological effects of NGF (Landrath et al, 1985). The specificity of WGA is relative rather than absolute.…”
Section: Discussionmentioning
confidence: 99%
“…In lymphocytes, Con A is a potent mitogen (Powell and Leon, 1970), and in adipocytes, both Con A and WGA mimic the action of insulin by binding directly to insulin receptors (Cuatrecasas and Tell, 1973;Shechter, 1983). In contrast, in PC12 pheochromocytoma cells, WGA inhibits nerve growth factor (NGF)-induced phosphorylation of a 250-kD cytoskeletal protein and NGF-induced neurite outgrowth at concentrations (2.5-10 Fgirnl) which have little effect on NGF binding (Landreth et al, 1985), and in rat pituitary cells, both WGA and Con A (10 pgiml) inhibit gonadotropin releasing hormoneinduced release of leuteinizing hormone (Schvartz and Hazum, 1986). In both PC12 cells and platelets, lectins induce attachment of cell surface proteins to the underlying cytoskeleton (Painter and Ginsberg, 1982;Vale and Shooter, 1982) but the relationship between this effect and the biological actions of lectins has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-surface receptors for hormones usually contain oligosaccharides, which are attached to asparagine residues in the external domain of the receptor (67)(68)(69). Cell-agglutinating, sugar-specific lectins bind the N-linked oligosaccharides of hormone receptors (67,(70)(71)(72)(73). Chen (39) screened a variety of lectins for an effect on Cd2+-evoked Ca2+ mobilization.…”
Section: The Putative Orphan Receptor Is a Plasma Membrane Sialoproteinmentioning
confidence: 99%